The Role of Intracellular Organisms in the Pathogenesis of Inflammatory Arthritis - Animesh Singh; Sarah Karrar (International Journal of Inflammation)
Inflammatory arthritis is a condition which is characterised by recurrent episodes of joint pain and swelling. It encompasses a spectrum of disorders ranging from rheumatoid arthritis to ankylosing spondylitis. In these conditions, for reasons that are poorly understood, the immune system raises an inflammatory response within the joint space. In some cases, autoantigens have been identified (e.g., anticitrullinated peptides in rheumatoid arthritis), but the absence of these, in the seronegative arthritides, for example, raises question as to the underlying pathogenesis. Interest has, therefore, turned to host-pathogen interactions and whether aberrant immune responses to these could explain the development of arthritis. This has been most widely studied in reactive arthritis (ReA), where an infectious episode precedes the development of the joint symptoms. In this review, we present the evidence for the role of host-bacterial interactions in the pathogenesis of joint inflammation with particular emphasis on ReA. We discuss a range of possible mechanisms including molecular mimicry, persistent low grade infections, and abnormal host responses to common bacterial causes of reactive arthritis as well as discussing some of the clinical challenges that we face in making the diagnosis and in treatment of persistent symptoms.